Development of a web-based reporting information system at PUSDATIN - Nisrina Labiba Sarwoko; Sembada Denrineksa Bimorogo (Jurnal Mandiri IT, 2026)
Reporting plays a vital role in documenting work results, evaluating performance, and supporting data-driven decision-making through the presentation of clear, systematic, and well-organised information. However, the reporting process within the Pusat Data dan Informasi (Pusdatin) of the Kementerian Pertahanan, particularly in the Division of Pengamanan Sistem Informasi dan Persandian (Pamsisinfosan), was still conducted conventionally using paper-based forms, resulting in scattered archives, inefficient data storage, and delays in accessing activity records. This study introduces a web-based digital reporting platform that transforms conventional activity reporting into an integrated digital system equipped with activity recording, employee data management, scheduling features, and centralized data storage. The research adopted the Rapid Application Development (RAD) approach, consisting of requirement analysis, system design, construction, and implementation stages. The system was developed using the Laravel framework with database migration, authentication management, and a responsive interface built using Tailwind CSS. The results show that the proposed system simplifies activity reporting, improves data organization, and facilitates faster access to reports and schedules for operational personnel. Practically, the system supports more efficient administrative management by replacing manual forms with structured digital records that are easier to manage and retrieve. In conclusion, the implementation of a web-based reporting system using the RAD approach enhances administrative efficiency and supports daily operational activities within the Pamsisinfosan Division of Pusdatin, Kementerian Pertahanan.